2010
DOI: 10.1093/schbul/sbq090
|View full text |Cite
|
Sign up to set email alerts
|

Modafinil Reverses Phencyclidine-Induced Deficits in Cognitive Flexibility, Cerebral Metabolism, and Functional Brain Connectivity

Abstract: Objective: In the present study, we employ mathematical modeling (partial least squares regression, PLSR) to elucidate the functional connectivity signatures of discrete brain regions in order to identify the functional networks subserving PCP-induced disruption of distinct cognitive functions and their restoration by the procognitive drug modafinil. Methods: We examine the functional connectivity signatures of discrete brain regions that show overt alterations in metabolism, as measured by semiquantitative 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(80 citation statements)
references
References 110 publications
(135 reference statements)
4
76
0
Order By: Relevance
“…Acute ketamine treatment disrupts brain networks N Dawson et al hypofrontality characteristic of the disorder (Cochran et al, 2003;Dawson et al, 2012Dawson et al, , 2014, whereas acute ketamine treatment induces a contrasting hyperfrontality, a paradox that is yet to be resolved given the schizophrenia-like symptoms induced by acute ketamine treatment. It may be the case that ketamine-induced alterations in functional brain network structure have the greatest translational relevance to those symptoms present during acute psychotic episodes rather than those that remain present in chronic schizophrenia patients treated with antipsychotics.…”
Section: Discussionmentioning
confidence: 99%
“…Acute ketamine treatment disrupts brain networks N Dawson et al hypofrontality characteristic of the disorder (Cochran et al, 2003;Dawson et al, 2012Dawson et al, , 2014, whereas acute ketamine treatment induces a contrasting hyperfrontality, a paradox that is yet to be resolved given the schizophrenia-like symptoms induced by acute ketamine treatment. It may be the case that ketamine-induced alterations in functional brain network structure have the greatest translational relevance to those symptoms present during acute psychotic episodes rather than those that remain present in chronic schizophrenia patients treated with antipsychotics.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, four animal model studies of cognitive deficits showed significant improvements with modafinil [Dawson et al 2010;Goetghebeur and Dias, 2009;Pedersen et al 2009;Redrobe et al 2010]. In humans, four single-dose crossover RCTs showed significant positive effects of modafinil on executive functioning, verbal memory span, visual and working memory, spatial planning, slowing in latency, impulse control and recognition of faces expressing sadness and sadness misattribution in the context of disgust recognition Scoriels et al 2011;Spence et al 2005;Turner et al 2004].…”
Section: Fatigue Sleepiness and Activity Levelsmentioning
confidence: 83%
“…Administration of subchronic phencyclidine (PCP) to rats is used as an animal model for executive functioning deficits in schizophrenia. When PCP was administrated to rats an ID/ED shift deficit was induced and when these rats were treated with modafinil, the ID/ED shift deficit improved significantly [Dawson et al 2010;Goetghebeur and Dias, 2009;Pedersen et al 2009]. Neuroimaging showed that acute modafinil treatment effectively reversed distinct PCPinduced alterations in overt cerebral metabolism in the anterior prelimbic cortex, the retrosplenial cortex and the medial prelimbic cortex (layer 1).…”
Section: Fatigue Sleepiness and Activity Levelsmentioning
confidence: 99%
See 2 more Smart Citations